Developmental Status of Toddlers Aged 1–3 Years Assessed Using the Denver Developmental Screening Test at a Tertiary Care Hospital in Haryana, India - Ms. Sandeep Kaur; Dr. Jyoti Sarin; Ms. Mehak; Mr. Kushal; Mr. Lucky; Mr. Lakhan (The Bioscan, 2026)
Objectives: To assess the developmental status of toddlers aged 1–3 years using the Denver Developmental Screening Test (DDST) and examine its association with selected socio-demographic variables. Methods: A descriptive cross-sectional study was conducted in the Pediatric Outpatient Department and Pediatric Medicine Ward of MMIMS&R Hospital, Mullana, Ambala, Haryana. Using purposive sampling, 110 toddlers aged 1–3 years were enrolled. Data were collected through a socio- demographic questionnaire and DDST performa. Descriptive statistics and Chi-square tests were applied for analysis. Results: Most toddlers were 20–27 months old (38.2%); 52.7% were males. The majority were term- born (81.8%) with normal birth weight (83.6%). The highest mean DDST score was in Gross Motor (15.1 ± 1.9) and the lowest in Language (12.9 ± 2.8). Overall, 23% showed suspected developmental delay. Significant associations were found with gestational age (p = 0.02), birth weight (p = 0.04), and caregiver education (p = 0.01). Conclusion: Nearly one-fourth of toddlers had suspected developmental delay, especially in language. Routine DDST screening is recommended for early detection and intervention.